2021
DOI: 10.1021/acsnano.1c05268
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Production of 1T MoS2 Monolayers Based on Controllable Conversion of Mo-Based MXenes

Abstract: Although transition metal dichalcogenides (TMDs) monolayers are widely applied in electronics, optics, catalysis, and energy storage, their yield or output is commonly very low (<1 wt % or micrometer level) based on the well-known top-down (e.g., exfoliation) and bottom-up (e.g., chemical vapor deposition) approaches. Here, 1T MoS 2 monolayers with a very high fraction of ∼90% were achieved via the conversion of Mo-based MXenes (Mo 2 CT x and Mo 1.33 CT x ) at high temperatures in hydrogen sulfide gas, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 48 publications
(77 reference statements)
0
25
0
Order By: Relevance
“…[13][14][15] Recently, a series of materials with conductive and catalytic functions have been used as additives for the cathode of Sulfur to accelerate the conversion of polysulfides and regulate the kinetics of the reactions. [16][17][18][19][20][21][22][23][24] Cobalt dichalcogenide has been applied previously as an efficient catalyst to ameliorate the kinetics of polysulfide conversion, [25][26][27][28][29] in which the metal cation forms an octahedral complex with dimers such as S 2 2− , Se 2 2− , or Te 2 2− in a low-spin energy state, while the 3d orbital of cobalt ion splits into two subordinate orbitals t 2g and e g upon the crystal field force. For cobalt ditelluride (CoTe 2 ), since the 3d electron configuration of cobalt takes the low spin of t 2g 6 e g 1 , CoTe 2 has good metallic conductivity, which can promote the rapid charge transfer for the electrode, and contribute to catalyzing the conversion of polysulfides.…”
Section: Doi: 101002/adma202204403mentioning
confidence: 99%
“…[13][14][15] Recently, a series of materials with conductive and catalytic functions have been used as additives for the cathode of Sulfur to accelerate the conversion of polysulfides and regulate the kinetics of the reactions. [16][17][18][19][20][21][22][23][24] Cobalt dichalcogenide has been applied previously as an efficient catalyst to ameliorate the kinetics of polysulfide conversion, [25][26][27][28][29] in which the metal cation forms an octahedral complex with dimers such as S 2 2− , Se 2 2− , or Te 2 2− in a low-spin energy state, while the 3d orbital of cobalt ion splits into two subordinate orbitals t 2g and e g upon the crystal field force. For cobalt ditelluride (CoTe 2 ), since the 3d electron configuration of cobalt takes the low spin of t 2g 6 e g 1 , CoTe 2 has good metallic conductivity, which can promote the rapid charge transfer for the electrode, and contribute to catalyzing the conversion of polysulfides.…”
Section: Doi: 101002/adma202204403mentioning
confidence: 99%
“…Ni-N 5 /HNPC/S 1188 mAh g -1 at 0.2 C 684 mAh g -1 at 4 C 1 m LiTFSI in DOL/DME with 0.1 m LiNO 3 [13] Fe-N-C Mesocellular carbon foam Fe-N-C/S-MCF 1244 mAh g -1 at 0.1 C 798 mAh g -1 at 5 C 1 m LiTFSI in DOL/DME with 2% LiNO 3 [14] Co 4 W 18 Clusters Co 4 W 18 /rGO 1426 mAh g -1 at 0.05 C 644 mAh g -1 at 5 C 0.5 m LiTFSI and 0.5 m LiNO 3 in DOL/ DME [15] P-doped NiTe 2 Nanosheet MSC/P⊂NiTe 2− 1318 mAh g -1 at 0.2 C 764 mAh g -1 at 5 C 1 m LiTFSI in DOL/DME [16] Fe 2 O 3 /N-MC Hierarchical structure S@Fe 2 O 3 /N-MC, 1172 mAh g -1 at 0.2 C 740 mA h g -1 at 5 C 1 m LiTFSI in DOL/DME with 1% LiNO 3 [17] Co 9 S 8 /Co Nanoparticle Li 2 S-Co 9 S 8 /Co 1006 mAh g -1 at 0.1 C 616 mAh g -1 at 4 C 1 m LiTFSI and 0.2 m LiNO 3 in tetraglyme [18] Ti 3 C 2 MXene Nanosheet S/3D e-Ti 3 C 2 -2 1205.9 mAh g -1 at 0.2 C 772.4 mAh g -1 at 5.0 C 1 m LiTFSI in DOL/DME with 1% LiNO 3 [19] MoS 2 Monolayer MoS 2 -500 532 mAh g -1 at 5.0 C 1 m LiTFSI in DOL/DME with 2% LiNO 3 [20] Halloysite TiO 2 Nanoparticle SC-TiO 2 -Hal/S 1037.6 mAh g -1 at 0.2 C 566.9 mAh g -1 at 5.0 C 1 m LiTFSI in DOL/DME with 0.1 m LiNO 3 [21] TiC Nanoparticle TiC@CNF/S 1058 mAh g -1 at 0.2 C 738 mAh g -1 at 5.0 C 1 m LiTFSI in DOL/DME with 2% LiNO 3 [22] NiO-Ni 3 N Nanoparticle NiO-Ni 3 N-AC-S 1179 mAh g -1 at 0.2 C 652 mAh g -1 at 4.0 C 1 m LiTFSI in DOL/DME with 1% LiNO 3 [23] Borophene sheets CNT/B 1329 mAh g -1 at 0.2 C 919 mAh g -1 at 4.0 C 1 m LiTFSI in DOL/DME with 1% LiNO 3 [24] TiNb 2 O 7 Nanoparticle ACC@TNO 1399 mAh g -1 at 0.1 C 885 mAh g -1 at 4.0 C 1 m LiTFSI in DOL/DME with LiNO 3 [25] In 2 S 3−x Marigold-like Nanoparticle…”
Section: Li-s Batteriesmentioning
confidence: 99%
“…[22] The NbB 2 nanoparticles synthesized by Xu et al also demonstrated that the B-terminated is more inclined to interact with polysulfides anions rather than lithium ions, and the high electronic conductivity and catalytic effect of NbB 2 enable the 3D deposition of Li 2 S. [23] Besides, the corresponding batteries with CoB, [24,25] and ZrB 2 [26,27] as sulfur hosts also exhibit excellent performance. However, the above reports do not mention how to improve the intrinsic catalytic properties of the borides, in addition, most of the metal atoms reported above are 3d and 4d metals, [28][29][30][31] while 5d metal electrons are reported to have strong spin-orbit coupling and could cause the p orbitals of nonmetallic atoms to locate closer to the Fermi level, which could regulate the transport of ion and electron, resulting in redox activity of anion and unconventional superconductivity of the compound.…”
Section: Introductionmentioning
confidence: 99%